2019
DOI: 10.1111/jch.13543
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on the blood pressure–lowering effect of amlodipine and nifedipine‐GITS in sustained hypertension

Abstract: In a multicenter, randomized trial, we investigated whether the long half‐time dihydropyridine calcium channel blocker amlodipine was more efficacious than the gastrointestinal therapeutic system (GITS) formulation of nifedipine in lowering ambulatory blood pressure (BP) in sustained hypertension (clinic systolic/diastolic BP 140‐179/90‐109 mm Hg and 24‐hour systolic/diastolic BP ≥ 130/80 mm Hg). Eligible patients were randomly assigned to amlodipine 5‐10 mg/day or nifedipine‐GITS 30‐60 mg/day. Ambulatory BP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…14 Huang et al assessed the efficacy of amlodipine and nifedipine-GITS by comparing the reduction of SBP and DBP means with the univariate approach and found similar reduction which might be different if correlation accounted. 15 The correlation among the variables plays a major role in decision making; in this analysis at 84th month of follow-up, both SBP and DBP means were statistically similar in univariate and bivariate approaches with observed correlation among them (r = 0.514). But a little shift of correlation from 0.514 to 0.571, the decision of bivariate approach changed in contrast to univariate, suggesting decisions are sensitive towards correlation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…14 Huang et al assessed the efficacy of amlodipine and nifedipine-GITS by comparing the reduction of SBP and DBP means with the univariate approach and found similar reduction which might be different if correlation accounted. 15 The correlation among the variables plays a major role in decision making; in this analysis at 84th month of follow-up, both SBP and DBP means were statistically similar in univariate and bivariate approaches with observed correlation among them (r = 0.514). But a little shift of correlation from 0.514 to 0.571, the decision of bivariate approach changed in contrast to univariate, suggesting decisions are sensitive towards correlation.…”
Section: Discussionmentioning
confidence: 53%
“…14 The effectiveness of amlodipine against the nifedipine in lowering ambulatory BP in sustained hypertension was investigated and compared between the groups at the base, 4-week, and 8-week using unpaired t-test. 15 Similarly Chen et al in one randomized trial of 8 weeks investigated efficacy and tolerability of initial high (5.0 mg/d) vs. low (2.5 mg/d) doses of S-(− )amlodipine in hypertension. The univariate unpaired t-test was applied to compare the mean change of clinic as well as ambulatory BP between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the incidence of adverse events was similar between the two groups. However, after missing a dose of medication, greater reduction in 24‐hour DBP (nifedipine GITS vs amlodipine = ‐4.3 vs ‐5.5 mmHg, P = .04) and daytime DBP (nifedipine GITS vs amlodipine = ‐4.5 mmHg vs. ‐6.0 mmHg, P = .02) was observed in the amlodipine group, indicating that when a dose is delayed for hours on monotherapy, the efficacy of nifedipine GITS might be reduced markedly 13 …”
Section: Discussionmentioning
confidence: 92%
“…Fiscal outcomes compared with both the gastrointestinal therapeutic system (GITS) and the osmotic‐controlled release oral delivery system (OROS) of nifedipine use osmotic pressure as the driving force to deliver drugs through laser‐drilled holes, providing stable drug concentrations, uniform drug effect, and reduced dosing frequency 11,12 . Furthermore, with regard to clinical efficacy, application of extended‐release formulations of nifedipine demonstrated similar blood pressure (BP)‐lowering effects as long‐acting amlodipine 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…38 Huang et al reported that amlodipine was more efficacious (2–3 mm Hg) than nifedipine in reducing the 24-hour BP when the dose of medication got missed. 39 A phase IV study investigated the effect of amlodipine/valsartan on the mean 24-hour ambulatory BP when given in the morning (6–10 am ) and evening (6–10 pm ). Following 4 weeks of treatment, the patients who took dose in morning, and evening showed a mean reduction of −12.16 (0.88)/− 11.17 (0.90) mm Hg in SBP, respectively while the reduction of DBP in morning, and evening was −7.71 (0.59) and −7.01 (0.60) mm Hg, respectively.…”
Section: Amlodipine: Blocks All Types Of Calcium Channelsmentioning
confidence: 99%